A numerical treatment of the symmetry boundary condition via the finite gradient in the coordinate-free form. (29th August 2007) - Kim, C.-J.; Ro, S. T.
A survey of literature reveals that available textbooks discuss the symmetry boundary conditions mainly with the orthogonal control volumes, probably because detailed discussion calls for a complicated coordinate transformation. In the present work, the symmetry boundary conditions are treated via the finite gradient recently developed. The compactness and clarity acquired by employing the finite gradient are noteworthy in handling the non-orthogonal control volumes.